Revolutionary developments in the world economy - Horst Hanusch (Universität Augsburg, Institut für Volkswirtschaftslehre, 2016)
In the last decades the world changed dramatically. From a global point of view three disruptive processes are on their way which can be called revolutionary: a political, a technological and an economic revolution. This paper aims to give an overview when and how these movements started what the essence of these processes is and with which consequences we will have to deal with in the future. Concerning the political revolution the year 1990 can be characterized as a historical landmark because of two reasons: At first, it finished with orthodox communism as it was practiced primarily in the former Soviet Union. Secondly, this year created a new illusion which is described at its best by Francis Fukuyama in his book "The End of History" (1990). The Western form of a liberal representative democracy had overruled communism as its most important counterpart and it promised to stay forever as a political system when combined with a capitalistic market economy. That means in last consequence "the end of history".The paper shows how this illusive thinking has been demolished in the last twenty years and in which way a new regime of political thinking, the "autocratic system" of political decision making, is gaining relevance worldwide in developed as well as in developing countries. Starting in China and spreading over to other countries in the second half of the last century it now even reached countries in Europe which after 1990 tried to install a liberal representative democracy with great empathy, for instance Russia, Hungary, the Czech Republic and recently also Poland. The paper tries to grasp this process, to find answers why the attractiveness of the democratic ideal is fading away in these days and to show which consequences this political transformation process might have for the global economy. The last two decades of the 20 th century set off a third great wave of technological invention and disruptive innovation, the "digital revolution". Radical advances in computing-, information- and communication-technology may deliver a similar mixture of transformation as societies had experienced in the centuries before, getting acquainted to the steam engine, electricity, the telegraph and telephone for instance. The larger part of economists and scientists today sticks to the opinion that this new technological revolution will change fundamentally essential characteristics of the three pillars which constitute a socio-economic system: the financial, the public and the real sector. [...]
urn:nbn:de:bvb:384-opus4-710733
Keywords: B52; O3; P10; 330; Development Economics; Institutional Theory; Technological Change; Schumpeterianism